Integrating Disturbance, Seasonality, Multi-Year Temporal Dynamics, and Dormancy Into the Dynamics and Conservation of Metacommunities - Holyoak, Marcel; Caspi, Tal; Redosh, Lauren W. (Frontiers in Ecology and Evolution, 2020)
The metacommunity framework has rapidly become a dominant concept used by ecologists to understand community assembly. By emphasizing extinction-colonization dynamics, dispersal, and species’ niche requirements in determining community structure, metacommunity theory unifies local and regional processes as integral to species distributions across landscapes. Metacommunity structure has traditionally been treated as static. However, habitat characteristics and community composition can shift through time because of factors like seasonal dynamics, ecosystem disturbance, multi-year climate variation (e.g., El Niño Southern Oscillation), and production and emergence of dormant propagules. In most systems, the relevance of such temporal variation for the structure and persistence of metacommunities is an open question that is of potential importance for conservation and management. We evaluate and synthesize the theory and concepts relevant to four major forms of temporal dynamics that are pertinent to metacommunities: disturbance, seasonality, multi-year climate variation, and dormancy. For each type of dynamic we review the theoretical underpinnings and empirical evidence to evaluate how the dynamic drives temporal variation in metacommunity structure. We also consider how major forms of anthropogenic change further influence these patterns. Our survey highlights that seasonal climatic differences can modify the distribution and availability of resources and connectivity, with consequences for species’ use of the landscape and species interactions. Disturbance and multi-year climate cycles can increase the importance of dispersal, but implications for environmental filtering and species interactions remain unresolved. Dormant life stages serve to anchor habitat patches and species pools in space and highlight the importance of dispersal-dormancy tradeoffs and environmental variation for metacommunity structure. Temporal variability in biotic and abiotic conditions associated with these drivers can modify the relative strengths of dispersal, environmental filtering, and species interactions, three biological processes that drive metacommunity structure. Inclusion of spatiotemporal drivers creates patterns of species diversity that differ from traditional metacommunity ideas. We use these insights to highlight research needs, suggest a reconceptualization of metacommunities as undergoing continuous change, and discuss the implications of temporal dynamism for the conservation and management of metacommunities.